Prodromus of a fern flora for Bolivia. XXIII. Saccolomataceae - Kessler, Michael; Smith, Alan R. (Phytotaxa, 2017)
We provide a synopsis to the monogeneric fern family Saccolomataceae in Bolivia, comprising three widespread species.